The Effectiveness of Personal Vocabulary Note (PVN) Technique through Al-Qur’an in Improving Students’ English Vocabulary - Syayyidina Ali; Mutmainnah Marzuki (Universitas Sulawesi Barat, 2021)
A good technique is required by the students to help them in acquring, extending and developing their English vocabulary. The aims of this research is to investigate the effects of personal vocabulary note (PVN) technique through Al-Qur'an in improving students' English vocabulary mastery. This study was an experimental model consisting of two groups: experimental and control group; it was conducted at Islamic Boarding School of Babul Khaer Kalumeme Bulukumba, South Sulawesi. Samples of the study were 30 students, 15 students were experimental group and 15 students were control group. The data were collected with pre-test, treatment and post-test. Writeen vocabulary test was administered to both groups of experimental and control; and it was analyzed and interpreted by means of SPSS 18.0 program. The results of the research indicated that personal vocabulary note technique through Al-Qur'an gives significant effect on students' vocabulary improvement. The result of the students' vocabulary score improvement from pre-test to post-test demonstrated significant differences. The research found that sig. (2-tailed) is 0.000 lower than 0.05. Comparison of the students' improvement beteween the two groups was 0.000 which meant that the improvement was significant.